Ossification: a new approach to immobilize metal complex catalysts - applications to carbonylation and Suzuki coupling reactions - Sarkar, Bibhas R.; Chaudhari, Raghunath V. (Journal of Catalysis, 2006)
A simple approach for immobilization of transition metal complexes is reported here based on the transformation of the complex into its intrinsically insoluble counterpart, thus generating solid molecular catalysts. This approach that we call ``ossification'' is based on a principle, in which the water-soluble analogues of the metal complexes are precipitated out from aqueous solutions as insoluble ionic ensembles having catalytically active metal-centered coordination environments and robust framework. The approach has been illustrated for I'd complex catalyzed carbonylation and Suzuki coupling reactions. ``Ossification'' was found to be an economically and environmentally attractive alternative to other exotic immobilization methodologies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Carbonylation; Heterogeneous catalysts; Immobilization; ossification; Palladium complex; Suzuki coupling